1991
DOI: 10.1016/0014-5793(91)81402-t
|View full text |Cite
|
Sign up to set email alerts
|

A novel alternatively spliced viral mRNA transcribed in cells infected with human T cell leukemia virus type 1 is mainly responsible for expressing p21X protein

Abstract: The pX sequcncc of human T cell Icukcmia virus type I (HTLV-I) has been thought to bc cxprcsscd as a doubly spliced mRNA thal codes for p40lax. p27rcx and p21X. However. WC identified a novel allcrnativcly spliced mRNA in the HTLV-I infccvd cells by using rcvcrsc transcription rollowed by the polymcrasc chain rcaction. This mRNA conlains only the firs1 and third cxons of the doubly spliced mRNA and encodes only p2lX. Our data thaw this mRNA is rcsponsiblc for expressing p2lX exists in most or HTLV-I infcclcd c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 43 publications
3
39
0
Order By: Relevance
“…Since the natural occurring splice variant Rexp21 (Berneman et al, 1992;Bhat et al, 1993;Orita et al, 1991) was reported to be transdominant (Kubota et al, 1996) we constructed a Rexp21-GFP hybrid protein. Rexp21 is lacking the ®rst 78 N-terminal amino acids, including the RNAbinding domain and the nuclear localization signal (NLS).…”
Section: Localization Of Rex-gfp Hybrid Proteins In Living Human Cellsmentioning
confidence: 99%
“…Since the natural occurring splice variant Rexp21 (Berneman et al, 1992;Bhat et al, 1993;Orita et al, 1991) was reported to be transdominant (Kubota et al, 1996) we constructed a Rexp21-GFP hybrid protein. Rexp21 is lacking the ®rst 78 N-terminal amino acids, including the RNAbinding domain and the nuclear localization signal (NLS).…”
Section: Localization Of Rex-gfp Hybrid Proteins In Living Human Cellsmentioning
confidence: 99%
“…x protein itself have been detected in various HTLV-I-infected cell-lines and uncultured primary adult T-cell leukemic cells (Berneman et al, 1992;Furukawa et al, 1991;Orita et al, 1991). Although these data may indicate some involvement for p21…”
Section: Resultsmentioning
confidence: 94%
“…RT/TS-PCR was carried out as described previously (Orita et al, 1991). Briefly, 0-5 Izg of total RNA was annealed with 500 ng of a random hexadeoxynucleotide primer, reverse-transcribed using 15 units of AMV reverse transcriptase at 42 °C for 1 h, and 8.3 ~tl of 6 x PCR buffer (1 x PCR buffer consists of 16-6 mM-ammonium sulphate, 67 mM-Tris-HC1 pH 8.8 at 25 °C, 6-7 mM-magnesium chloride, 10 mM-2-mercaptoethanol, 7-7 p.M-EDTA and 170 ~tg/ml BSA), 5 p.1 each of 15 mM-dATP, 15 mM-dCTP, 15 mM-dGTP and 15 mM-TTP, and 1 pmol of the PCR primers PX1 and PX2 were then added to the reaction vessel to give a final volume of 50 p.l.…”
Section: Quantitative Rt/two Step Pcr (Rt/ts-pcr)mentioning
confidence: 99%
“…In contrast to this concept, we have recently discovered a novel, alternatively spliced mRNA capable of specifically expressing p21X (named p21X mRNA) in most HTLV-l-infected cell lines by using a highly sensitive method involving a polymerase chain reaction (PCR) coupled to reverse transcription (RT-PCR) (Orita et al, 1991).…”
Section: Introductionmentioning
confidence: 99%